2022
DOI: 10.1021/acs.est.2c04245
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Resistance: Quantifying the Relationship between Urban Development, Agricultural Pesticide Use, and Pesticide Resistance in a Nontarget Amphipod

Abstract: Resistance alleles within the voltage-gated sodium channel (vgsc) have been correlated with pyrethroid resistance in wild populations of the nontarget amphipod, Hyalella azteca from California (CA), U.S.A. In the present study, we expand upon the relationship between land use and the evolution of pesticide resistance in H. azteca to develop a quantitative methodology to target and screen novel populations for resistance allele genotypes in a previously uninvestigated region of the U.S. (New England: NE). By in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…It is possible that nontarget Lepidopterans could also develop resistance to permethrin. Resistance development in pest Lepidopteran species has been reported (Jia et al 2009 ; Grigg-McGuffin et al 2015 ; Uesugi 2020 ; Sun et al 2022 ) and has been reported in a nontarget aquatic invertebrate (Major et al 2022 ). The common aspect of this resistance development is that it occurs in organisms either targeted by the applications or are unintentionally routinely exposed to the insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that nontarget Lepidopterans could also develop resistance to permethrin. Resistance development in pest Lepidopteran species has been reported (Jia et al 2009 ; Grigg-McGuffin et al 2015 ; Uesugi 2020 ; Sun et al 2022 ) and has been reported in a nontarget aquatic invertebrate (Major et al 2022 ). The common aspect of this resistance development is that it occurs in organisms either targeted by the applications or are unintentionally routinely exposed to the insecticide.…”
Section: Discussionmentioning
confidence: 99%
“…However, developing resistant varieties and biological control approaches takes time. More importantly, Xcc is now resistant to the vast majority of chemicals, including copper‐based formulations, 7 and overused pesticides accumulate in the environment, leading to further resistance build‐up and toxicity for the environment and humans 8–10 . For these reasons, there is significant interest in the development of efficient control technologies based on nanomaterials to combat citrus canker.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of terpenoid pheromones in species from North and South America belonging to the acanthocinini and acanthurini tribes, which are made up of certain enantiomers of related substances in nonracemic ratios, as well as the structurally related molecule certain 6-methylhept-5-en-2-one (sulcatone), nonracemic ratios of their enantiomers, 6,10-dimethyl-5,9- undecadien-2-ol (fuscumol), its acetate ester, 6-methylhept-5-en-2-ol may also be present in 6-methylhept-5-en-2-one (sulcatol), and 6,10-dimethyl-5,9- undecadien-2-yl acetate (fuscumol acetate) as shown in ( Figure 1 ). Chemical pesticides are the primary methods used to decrease vector mosquito populations ( Major et al, 2022 ), despite their limited availability due to environmental harm and non-target creatures ( Mulkiewicz et al, 2021 ). The utilisation of chemical insecticides presents greater difficulties and a variety of possible environmental issues, including their widespread emergence and their resistance to and interference with organic biological regulation mechanisms ( Reyes-Calderón et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%